Antibacterial, anti-biofilm and in vivo activities of the antimicrobial peptides P5 and P6.2. (February 2020) - Martínez, Melina; Polizzotto, Axel; Flores, Naiquén; Semorile, Liliana; Maffía, Paulo César
Abstract: Cationic antimicrobial peptides (AMPs) are short linear amino acid sequences, which display antimicrobial activity against a wide range of bacterial species. They are promising novel antimicrobials since they have shown bactericidal effects against multiresistant bacteria. Their amphiphilic structure with hydrophobic and cationic regions drives their interaction with anionic bacterial cytoplasmic membranes, which leads to their disruption. In this work two synthetic designed AMPs, P5 and P6.2, which have been previously analyzed in their ability to interact with bacterial or eukaryotic membranes, were evaluated in their anti-biofilm and in vivo antibacterial activity. In a first step, a time-kill kinetic assay against P. aeruginosa and S. aureus and a curve for hemolytic activity were performed in order to determine the killing rate and the possible undesirable toxic effect, respectively, for both peptides. The biofilm inhibitory activity was quantified at sub MIC concentrations of the peptides and the results showed that P5 displayed antibiofilm activity on both strains while P6.2 only on S. aureus . Scanning electron microscopy (SEM) of bacteria treated with peptides at their MIC revealed protruding blisters on Gam-negative P. aeruginosa strain, but almost no visible surface alteration on Gram-positive S. aureus . These micrographs highlighted different manifestations of the membrane-disrupting activity that these kinds of peptides possess. Finally, both peptides were analyzed in vivo, in the lungs of neutropenic mice previously instilled with P. aeruginosa . Mice lungs were surgically extracted and bacteria and pro-inflammatory cytokines (IL-β, IL-6 and TNF-α) were quantified by colony forming units and ELISA, respectively. Results showed that instillation of the peptides produced a significant decrease in the number of living bacteria in the lungs, concomitant with a decrease in pro-inflammatory cytokines. Overall, the results presented here suggest that these two new peptides could be good candidates for future drug development for anti-biofilm and anti-infective therapy. Highlights: Two novel AMPs P5 and P6.2 were analyzed in P.aeruginosa and S. aureus . Scanning electron microscopy revealed distinct membranolytic activity. Both peptides display in vitro antibiofilm activity. Peptides diminished P.aeruginosa burden in the lungs of neutropenic mice. P5 and P6.2 diminished lung pro-inflammatory cytokines.